Personality as a correlate of pronunciation attainment: The case of formal setting with explicit pronunciation-focused instruction - Baran-Lucarz, Małgorzata (Neofilolog, 2024)
The paper reports a study examining which Big Five personality traits correlate with pronunciation attainment of students who had been offered systematic long-term explicit pronunciation-focused instruction. The participants were 47 English majors just finishing their one-year course of practical English phonetics at the University of Wrocław, Poland. The five personality traits were measured with the use of a Polish version of Goldberg’s instrument, i.e. IPIP-BFM-50 (Struś, Cieciuch, Rowiński, 2014). The personality traits were then correlated with the students’ pronunciation proficiency represented by their (1) phonological competence, (2) pronunciation of selected vocabulary, and (3) accuracy in pronunciation operationalised as correct production of selected segments, rhythm, and consistency in using a chosen native English accent (RP or GA) when reading aloud a short passage with focus on its meaning. All of the judged aspects of pronunciation were explicitly drawn attention to and practised during the course of phonetics. The results of correlation analyses revealed that Openness to experience and Conscientiousness were significantly and positively linked to pronunciation attainment, with the former showing moderate and large effect sizes, and the latter, small and moderate effect sizes.